Perceived overqualification and employee outcomes: The dual pathways and the moderating effects of dual‐focused transformational leadership - Liu, Zhiqiang; Huang, Yuqi; Kim, Tae‐Yeol; Yang, Jing (Human Resource Management, 2024)
AbstractResearch findings concerning the effects of perceived overqualification on task performance are mixed. To reconcile the disparate findings, drawing on person‐environment theory, we propose cynicism toward the job and constructive deviance as contrasting dual pathways that explain the negative and positive effects of perceived overqualification on task performance and employee creativity. We also examine the moderating effects of dual‐focused transformational leadership (TFL) on the relationships between perceived overqualification and the two mediating mechanisms. We test this model using data collected from 469 employees and their 135 supervisors via two‐wave surveys. The results support the negative and positive mediating mechanisms. In addition, based on one field study and two online experiments, we find that individual‐focused TFL mitigates the relationship between perceived overqualification and cynicism toward the job, but that team‐focused TFL enhances the relationship between perceived overqualification and constructive deviance.